2012
DOI: 10.1007/s10886-012-0066-1
|View full text |Cite
|
Sign up to set email alerts
|

Diet Quality Can Play a Critical Role in Defense Efficacy against Parasitoids and Pathogens in the Glanville Fritillary (Melitaea cinxia)

Abstract: Numerous herbivorous insect species sequester noxious chemicals from host plants that effectively defend against predators, and against parasitoids and pathogens. Sequestration of these chemicals may be expensive and involve a trade off with other fitness traits. Here, we tested this hypothesis. We reared Glanville fritillary butterfly (Melitaea cinxia L.) larvae on plant diets containing low- and high-levels of iridoid glycosides (IGs) (mainly aucubin and catalpol) and tested: 1) whether IGs affect the herbiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 59 publications
1
42
1
Order By: Relevance
“…After parasitization by M. mediator , the encapsulation ability was decreased under elevated CO 2 during all measured time intervals, whereas the encapsulation ability was not significantly affected by decreases in the quality of wheat grown under the elevated CO 2 in this study. Different from our results, Laurentz et al (2012)33 showed that diet quality (increased catalpol concentrations) influences the encapsulation capability of Melitaea cinxia to defend against parasitoids and pathogens. Clearly, plant nutritional traits including primary- and secondary-chemistry affect the immune responses of herbivore insects.…”
Section: Discussioncontrasting
confidence: 99%
“…After parasitization by M. mediator , the encapsulation ability was decreased under elevated CO 2 during all measured time intervals, whereas the encapsulation ability was not significantly affected by decreases in the quality of wheat grown under the elevated CO 2 in this study. Different from our results, Laurentz et al (2012)33 showed that diet quality (increased catalpol concentrations) influences the encapsulation capability of Melitaea cinxia to defend against parasitoids and pathogens. Clearly, plant nutritional traits including primary- and secondary-chemistry affect the immune responses of herbivore insects.…”
Section: Discussioncontrasting
confidence: 99%
“…For example, oxidation of the phytochemical, chlorogenic acid, during insect chewing of plant material produces chlorogenoquinone, which can inactivate a baculovirus by binding to viral occlusion bodies and inhibiting the release of infective virions in the midgut (Felton & Duffey, 1990). Host-plant quality can also strongly influence insect susceptibility indirectly by altering insect physiology and the level of general immune measures, such as phenoloxidase activity, haemocyte numbers and the encapsulation rate (Klemola et al, 2007;Shikano et al, 2010;Laurentz et al, 2012). Few studies have focused on the importance of host-plant quality prior to pathogen exposure, but phytochemicals and nutrients are known to alter levels of constitutive immunity and physical barriers to pathogens that prevent or reduce the establishment of infection.…”
Section: Introductionmentioning
confidence: 99%
“…Diet quality can also greatly affect the physiological condition and immunocompetence of hosts (Fellous and Lazzaro ; Laurentz et al. ). We found that plantain diet increased larval survival only within more resistant, “high melanin” selection line (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…; Laurentz et al. ). In this study, we used P. plantaginis larvae from two selection lines for low or high amount of cuticular melanin.…”
Section: Introductionmentioning
confidence: 97%